(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This study aimed at determining the effects of caregivers’ training program on preschoolers’ cognitive readiness for transition from kindergarten to primary one in Rivers State Nigeria. The study adopted quasi-experimental non-equivalent pre-test and post-test design. The population of the study comprised 550 pupils and 78 teachers of pre-primary level. A sample of 111 pupils 48 (experimental) and 73 (control) and 8 teachers were drawn from the population using a multi-stage sampling procedure. The instrument for data collection for this study was an observational rating scale titled: Rating Scale for Observation of Kindergarteners and Primary One Pupils Readiness and Transition (RASOKIPOPRAT). Data collected were analysed using mean and standard deviations to answer the research questions, while the hypotheses were tested using Analysis of Covariance (ANCOVA) at 0.05 set as the level of significance. The findings of the study indicated among others that: caregivers’ training program was effective in enhancing preschoolers’ cognitive readiness towards learning for transition from kindergarten to primary one; school type had little influence on preschoolers’ cognitive readiness to learn for transition from kindergarten to primary one. Based on the findings it was recommended among others that: educational planners should accompany the one-year pre-primary curriculum with a training manual for teachers for the effective implementation of the curriculum; regular and effective monitoring of pre-primary school environment should be taken more seriously to ensure compliance to minimum standards. These can help preschoolers get ready cognitively for learning in primary schools.